(untitled) (Research, Society and Development, 2021)
The Internet of Things has created a world connected through many different types of sensors, allowing objects from our everyday lives to be networked. However, as the amount of data generated by these devices increases, the risk of theft and tampering becomes even more relevant. To improve the level of security within the Internet of Things, Blockchain presents itself as a potential solution for data integrity. However, realizing the connection between IoT devices and Blockchain is a task of reasonable complexity. In this context, this work proposes an architecture for transparency of connectivity of Blockchain services in IoT Systems. This architecture seeks to provide the end user with the perception of using the proposed system as a single and fully centralized system, hiding the complexities of this integration. To this end, a study was conducted on the characteristics of Blockchain networks, presenting benefits in the implementation in Internet of Things systems and a study of the types of platforms and the most commonly used communication protocols. To evaluate the proposed architecture, a case study was conducted to analyze the perception of the end user in the use of the proposal and the level of transparency applied.